Contribution of 18-fluorodeoxyglucose positron emission tomography (FDG PET) imaging in the detection of underlying carcinoma in a woman with nonspecific mastitis - Hancerliogulları, Oguz; Ince, Semra; Senocak, Rahman; Ilgan, Seyfettin; Arslan, Nuri (Vojnosanitetski pregled, 2021)
Introduction. Differentiation between a malignancy and inflammatory process is still a diagnostic challenge. Mammography (MG) and ultrasonography (US) have low sensitivity and specificity in dense breasts in order to detect malignancy. On the other hand, malignant mass lesions can also be masked on magnetic resonance imaging (MRI) by diffuse inflammatory process. 18-fluorodeoxyglucose positron emission tomography (FDG PET) imaging can be a promising alternative imaging method in the evaluation of suspicious breast masses, especially in patients with accompanying inflammatory breast diseases. Case report. We report an atypical case of a patient suspected for malignancy in right breast on physical examination and radiologic findings in favor of mastitis. Neither MG nor US revealed any mass lesion consistent with malignancy. Moreover, MRI findings were primarily considered as infectious or granulomatous mastitis. However, FDG PET determined the accurate borders of tumor and dissemination of breast cancer with superiority to other conventional radiological methods. Conclusion. This case report emphasizes the contribution of FDG PET imaging to other conventional radiological methods with regard to primary tumor diagnosis, determination of the biopsy site, and also staging the disease especially in patients with accompanying inflammatory breast disease. Introduction. Differentiation between a malignancy and inflammatory process is still a diagnostic challenge. Mammography (MG) and ultrasonography (US) have low sensitivity and specificity in dense breasts in order to detect malignancy. On the other hand, malignant mass lesions can also be masked on magnetic resonance imaging (MRI) by diffuse inflammatory process. 18-fluorodeoxyglucose positron emission tomography (FDG PET) imaging can be a promising alternative imaging method in the evaluation of suspicious breast masses, especially in patients with accompanying inflammatory breast diseases. Case report. We report an atypical case of a patient suspected for malignancy in right breast on physical examination and radiologic findings in favor of mastitis. Neither MG nor US revealed any mass lesion consistent with malignancy. Moreover, MRI findings were primarily considered as infectious or granulomatous mastitis. However, FDG PET determined the accurate borders of tumor and dissemination of breast cancer with superiority to other conventional radiological methods. Conclusion. This case report emphasizes the contribution of FDG PET imaging to other conventional radiological methods with regard to primary tumor diagnosis, determination of the biopsy site, and also staging the disease especially in patients with accompanying inflammatory breast disease.